Development of RNA interference-based therapy for rare genetic diseases - Milya Urfa Ahmad; Syarifah Dewi (Indonesian Society for Biochemistry and Molecular Biology, 2024)
In December 2022, the Indonesian Ministry of Health projected that rare diseases might affect 8–10% of the population, equating to approximately 27 million people. These diseases, often congenital, are linked to genetic inheritance or mutations, leading to structural or functional defects. Despite advancements in diagnostic and treatment methods, many rare diseases remain challenging for healthcare practitioners. RNA interference (RNAi) presents a promising therapeutic approach by enabling the selective inhibition of genes responsible for genetic disorders. RNAi employs small RNA molecules, such as small interfering RNA (siRNA) and microRNA (miRNA), to bind specific mRNA molecules and prevent their translation into proteins. Current research showed that RNAi-based therapies have the potential to treat various genetic diseases, including acute hepatic porphyria (AHP) and primary hyperoxaluria type 1 (PH1). However, the mechanisms of RNAi in hereditary disorders like AHP and PH1 require further documentation. RNAi offers several advantages, including gene-specific targeting, versatility in treating diverse genetic disorders, and scalability for mass production. Nonetheless, challenges remain, such as side effects, difficulties in targeting specific cells, and high development cost. Despite these obstacles, RNAi-based therapy holds significant potential for revolutionize the treatment of genetic disorders.